First Report on the Bioremediation of Textile Industrial Effluents by Piptoporus Betulinus IEBL-3 by Using Response Surface Methodology - Raja Tahir Mahmood; Muhammad Javaid Asad; Muhammad Asgher; Falak Sher Khan; Khursheed Muzammil; Nazim Nasir; Pervez Anwar; Muhammad Awais (Applied Sciences, 2022)
The current study was performed to optimize three different industrial textile effluent biodegradation potentials of a brown rot fungus, Piptoporus betulinus IEBL-3, to reduce environmental pollution. The Response Surface Methodology under the Box Bhenken Design was used for the optimization steps. Three ligninolytic enzymes named lignin peroxidase, manganese peroxidase and laccase were also studied during the biodegradation process. The biodegradation rate of the 3 industrial effluents varied between 67 and 76% at the initially optimized conditions. There was a 10%, 7% and 9% increase in the biodegradation of Mujahid textile (MT), Five Star textile (FST) and Sitara textile (ST) effluent, respectively, after the addition of various additional carbon and nitrogen sources in different ratios. The biological treatment decreases the Biological Oxygen Demand and Chemical Oxygen Demand values of the effluents well below the WHO-recommended values for the industrial effluents. The HPLC monitoring of the effluent’s biodegradation showed the appearance of new peaks, some of which may correspond to secondary amines. Study of ligninolytic enzymes during the biodegradation process confirmed their role in the biodegradation process, with lignin peroxidase having highest activity among the others. These findings suggest that P. betulinus is a potential fungus for the biodegradation of the dyes and effluents and can be a suitable candidate for this process.